PERBANDINGAN HUKUM INDONESIA DAN RUSIA TERHADAP ASAS KETERTIBAN UMUM DALAM PENETAPAN PUTUSAN ARBITRASE ASING BERDASARKAN UNCITRAL MODEL LAW - Sandy Sinatra Lubis (2021)
The Law on Arbitration and Alternative Dispute Resolution (APS) is Indonesia's arbitration law in order to guarantee legal certainty when conducting arbitration in Indonesia. In order to accommodate international arbitrations, the Arbitration Law and the APS regulate international arbitration awards. International arbitration judgements cause problems because they contradict the principle of public order. The results reveal that the UNCITRAL Model Law on International Commercial Arbitration on Reasons for Rejection, Recognition, and Implementation of Foreign Arbitration Decisions has exceptions to public order in article 66 letter (c) and also in article 36 paragraph 1 letter b(ii). According to the UNCITRAL MODEL LAW on International Commercial Arbitration, the recognition and implementation of an arbitral award can be rejected if it is determined that the award violates the country's public order provisions. However, the UNCITRAL MODEL LAW on International Commercial Arbitration does not provide a clear understanding of public order, so this is left to each country. The concept of public order in Indonesia is broadly interpreted, according to court rulings, and tends to stymie the arbitration process in Indonesia